Modeling ‘hard-to-measure’ costs in environmental management accounting / Michael Falta, Lynn Gallagher, and Roger Willett - Falta, Michael; Gallagher, Lynn (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
This paper reviews measurement issues that have arisen in the environmental management accounting literature and provides a statistical approach to quantifying the financial results associated with vaguely defined outcomes from physical processes. Among the latter are outcomes relating to safety and pollution both of which also impact on political visibility.